2003
DOI: 10.1103/physrevb.67.024208
|View full text |Cite
|
Sign up to set email alerts
|

Surface structure of Al-Pd-Mn quasicrystals: Existence of supersaturated bulk vacancy concentrations

Abstract: We identified the presence and chemical nature of bulk vacancies in Al-Pd-Mn quasicrystals by measuring the structure and composition of two-and fivefold cleavage surfaces of different preannealed quasicrystals subjected to postcleavage heat treatments using scanning electron microscopy and Auger electron spectroscopy. A strong dependence of the surface structure from the preannealing is observed and explained by varying concentrations of bulk vacancies. The analysis of the data shows that as-grown Al-Pd-Mn qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…10,34,35 Indeed, there is evidence that this type of diffusion eventually produces a vacancy-depleted near-surface region that is a few microns deep. 34 In that case, one would expect the voidrich terraces to occur early in the life of the sample and to disappear over time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,34,35 Indeed, there is evidence that this type of diffusion eventually produces a vacancy-depleted near-surface region that is a few microns deep. 34 In that case, one would expect the voidrich terraces to occur early in the life of the sample and to disappear over time.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the root-mean-square displacement of a bulk Mn atom ͑the slowest diffuser in this alloy͒ is 25 and 50 m, at temperatures of 900 and 950 K, over 3 h. 33 The fact that this displacement is very large and differs only by a factor of 2 over the temperature range 900-950 K supports the hypothesis that mass transport is extensive already at or below 900 K and does not change dramatically between 900 and 950 K. It has been suggested that surface modification due to migration of bulk defect vacancies also begins in a significantly lower temperature range. 10 Hence, it seems unlikely that new diffusion processes begin around 900 K.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Defects in crystalline solids-deviations from an idealized structure-have always been recognized as extremely important, since they can control fundamental properties such as mechanical strength, conductivity, color and corrosion. They affect surface properties as well, such as corrosion, nucleation, or phase selection [1,2]. The relationship between surface and bulk defects has emerged recently as a topic of great importance for understanding the unusual strength of nanostructures.…”
mentioning
confidence: 99%